ENTREPRENEURSHIP LEARNING BASED ON ETHNOPEDAGOGY: PREPARING STUDENTS OF ISLAMIC BOARDING SCHOOLS TO FACE THE ERA 5.0 - Thorida Nur Asih; M. Zainudin; Rahmatika Dewi (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
Abstrak: Pendidikan kewirausahaan telah menjadi topik penelitian yang berkembang sejak tahun 1989. Tujuan penelitian ini adalah untuk mengeksplorasi nilai-nilai yang digunakan sebagai dasar pembelajaran berbasis etnopedagogi. Selain itu, penelitian ini bertujuan untuk mengeksplorasi secara mendalam implementasi pembelajaran berbasis etnopedagogi di pondok pesantren sebagai upaya mempersiapkan santri menghadapi era 5.0. Penelitian kualitatif ini menggunakan metode studi kasus. Teknik pengumpulan data yang digunakan adalah dokumentasi, observasi dan wawancara. Data dalam penelitian ini dianalisis melalui reduksi data, penyajian data dan verifikasi. Hasil penelitian ini adalah 1) perkuliahan kewirausahaan berbasis etnopedagogi untuk mempersiapkan mahasiswa menghadapi era 5.0 dapat dilaksanakan dengan pemberian materi melalui diskusi studi kasus dan dilanjutkan dengan pemberian proyek untuk menyusun rencana bisnis, 2) nilai-nilai kewirausahaan yang dijadikan dasar etnopedagogi dalam perkuliahan kewirausahaan meliputi a) integrasi spiritualisme, b) moralitas, c) perencanaan bisnis, d) keberlanjutan sumber daya ekonomi, e) kreativitas, f) inovasi dan intuisi, g) manajemen, h) informasi dan risiko, i) kerjasama, j) titen, k) gemi, l) pethel, m) ora medit, n) sumeh, o) ora iri. Rencana bisnis terdiri dari identifikasi tujuan bisnis, penentuan sumber daya yang dibutuhkan, prediksi modal, identifikasi target pasar, pengukuran kinerja, identifikasi potensi kesalahan dan risiko, dukungan keputusan dukungan modal, dan pengurangan ketergantungan terhadap faktor eksternal.Abstract:  Entrepreneurship education has become a research topic that has developed since 1989. One of the implementations of entrepreneurship education is through ethnopedagogy-based entrepreneurship learning to foster self-confidence, develop creativity and innovation and dare to take risks for individuals which is implemented in Islamic boarding schools. The aim of this research is to explore the values used as the basis for ethnopedagogy-based learning. Apart from that, this research aims to explore in depth the implementation of ethnopedagogy-based learning in Islamic boarding schools as an effort to prepare students to face the 5.0 era. This qualitative research uses a case study method. The data collection techniques used are documentation, observation and interviews. The data in this research was analyzed through data reduction, data presentation and verification. The results of this research are 1) ethnopedagogy-based entrepreneurship lectures to prepare students to face the 5.0 era can be held by providing material through case study discussions and followed by providing projects to prepare business plans, 2) entrepreneurship values used as a basis for ethnopedagogy in entrepreneurship lectures include a) spiritualism integration, b) morality, c) business planning, d) economic resources sustainability, e) creativity, f) innovation and intuition, g) management, h ) informations and risks, i) cooperation, j) titen, k) gemi, l) pethel, m) ora medit, n) sumeh, o) ora iri. A business plan consists of identifying business objectives, determining required resources, capital prediction, target market identification, performance measurement, identification of potential errors and risks, capital support decision support, and reducing dependence on external factors.